An alarming presentation of bowel evisceration through ileostomy: a rare cause of small bowel obstruction (Indian Journal of Case Reports, 2025)
Stoma formation is a common procedure in colorectal surgery, often performed for conditions such as trauma, malignancy, and Crohn’s disease. One uncommon but potentially life-threatening consequence after stoma formation is bowel evisceration through the stoma. This case report presents a rare instance of small bowel obstruction caused by parastomal small bowel evisceration within a week of loop ileostomy creation in a 70-year-old female. The patient, who underwent ileostomy for decompression before planned radiotherapy for rectal cancer, presented with abdominal distension, pain, and bilious vomiting. Emergency surgery revealed herniation of the bowel through a wide opening in the rectus sheath, which was subsequently reduced after widening the stoma site. The case highlights the importance of careful stoma construction, as improper fixation or a large abdominal wall defect can lead to complications such as evisceration. Surgeons must ensure proper stoma formation to avoid this life-threatening consequence.